Testing the efficiency of the improved method of coproovoscopy for gastrointestinal nematodoses of dogs - Kitichenko, A. (Scientific Progress & Innovations, 2024)
Dogs are an important component of established parasitic systems. At the same time, the unregulated accounting system and the lack of data on their number in specific regions make it difficult to imagine the objective epizootological parameters of this population and, in particular, their epidemic danger. Parasitic systems function in the dog population, the co-members of which are gastrointestinal nematodoses, where the causative agents of trichurosis and uncinariosis are the most common. The aim of the work was to improve, test and determine the effectiveness of the method of lifelong coproovoscopic diagnosis of nematodoses of the digestive tract of dogs. The improved method refers to the field of veterinary medicine, namely veterinary parasitology, to methods of coproscopy, in particular, to methods of detecting eggs of causative agents of nematodoses of the digestive tract of dogs. We conducted tests of flotation methods of coproovoscopy, such as: Fulleborn’s, Kotelnikov-Khrenov’s, the method of coproovoscopy for trichurosis in sheep and the improved method for laboratory diagnosis of nematodoses of the digestive tract of dogs. It was found that 80 and 86.7 % of positive samples were detected for trichurosis and uncinariasis in dogs by the Fulleborn’s method, 93.3 and 100 % of positive samples were detected by the Kotelnikov-Khrenov’s method, and 100 % of positive samples were detected by the coproovoscopy method for sheep trichurosis and the improved method. When using the Fulleborn’s method, the indicators of the intensity of trichurosis and uncinariasis invasion were on average 69.7 and 44.9 eggs/g, Kotelnikov-Khrenov’s – 98.6 and 64.8 eggs/g, and the coproovoscopy method for sheep trichurosis – 106.7 and 68.0 eggs/g, improved method – 130.7 and 80.3 eggs/g. The improved method of lifelong coproovoscopy diagnosis of trichurosis and uncinariosis in dogs was more effective compared to the Fulleborn’s method by 46.7 and 44.1 %, Kotelnikov-Khrenov’s – by 24.6 and 19.3 %, the coproovoscopy method for sheep trichurosis – by 18.4 and 15.3 %. The improved method and method of coproovoscopy for trichurosis of sheep showed the highest coagulation properties in relation to undigested fodder residues, where a small amount of small undigested fodder residues surfaced during the research. The obtained results allow recommending an improved method of coproovoscopy for effective laboratory diagnosis of trichurosis and uncinariosis in dogs.